2022
DOI: 10.1149/10601.0063ecst
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pH on the Corrosion Behaviour for a Ni59.5 Nb40.5 Binary Metallic Glass

Abstract: Ni-Nb binary metallic glass was synthesized by the melt spinning technique with a tangential wheel rotation speed during cooling of 6 m/s obtaining a glassy matrix which was characterized by X-ray diffraction (XRD). Electrochemical properties were determined by electrochemical impedance spectroscopy (EIS). The results show that this metallic glass is very resistant to corrosion, being better when exposed to corrosive media with pH = 0 and 7 in chloride ions presence. However, at pH = 14 the passive film is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Several processes such as annealing, microalloying, and thermomechanical treatments have been carried out to improve the corrosion resistance of Ni-based BMGs as much as possible. For instance, Espinoza Vazquez et al [9] reported that NiNb amorphous alloy exhibited a superior corrosion resistance under the presence of chloride ions when the pH value was in the range of 0-7. On the other hand, the passive flm got inhomogeneous, and the corrosion rate increased at pH � 14.…”
Section: Introductionmentioning
confidence: 99%
“…Several processes such as annealing, microalloying, and thermomechanical treatments have been carried out to improve the corrosion resistance of Ni-based BMGs as much as possible. For instance, Espinoza Vazquez et al [9] reported that NiNb amorphous alloy exhibited a superior corrosion resistance under the presence of chloride ions when the pH value was in the range of 0-7. On the other hand, the passive flm got inhomogeneous, and the corrosion rate increased at pH � 14.…”
Section: Introductionmentioning
confidence: 99%